Longitudinal Improvements in Treatment Delivery Efficiency for MR-Guided Radiation Therapy: An 8-Year Single-Institution Experience - Robert A. Herrera; Sirikorn Unsri; Kathryn E. Mittauer; Rupesh Kotecha; Adeel Kaiser; Matthew D. Hall; Yongsook C. Lee; Yonatan Weiss; Tatiana Bejarano; Eyub Y. Akdemir; Mattison J. Flakus; Nikolai Strusberg-Fernandez; et al. (Cancers, 2026)
Purpose: While magnetic resonance-guided radiation therapy (MRgRT) may provide significant clinical advantages, delivery times tend to be longer than other radiation therapy (RT) modalities and published data on these times are limited. We evaluated longitudinal treatment times across our 8-year institutional MRgRT experience. Methods/Materials: A retrospective analysis of patients treated at our institution on a 0.35-Tesla MR-Linac between April 2018 and April 2026 was performed. All fractions were delivered with continuous intrafraction cine-MRI, soft tissue tracking, automatic beam gating, and online adaptive radiation therapy (oART) when indicated. The primary objective was to characterize changes in total in-room time (TIRT), treatment delivery time (TDT), and total adaptive time (TAT). For analysis of efficiency gains, our overall experience was separated into early (2018–2022) and late (2022–2026) periods. Results: A total of 1026 patients, 1203 treatment courses, and 7665 fractions were included. The median age was 69 years (range: 19–94) and the most commonly treated sites by treatment course were pancreas (n = 430; 35.7%), thorax (n = 203; 16.9%), abdominopelvic lymph nodes (n = 181; 15.0%), liver (n = 138; 11.5%), and adrenal gland (n = 83; 6.9%). The median prescription dose was 50 Gy (range: 16.0–76.0) in a median of five fractions (range: 1–36). Breath-hold and stereotactic body radiation therapy (SBRT) were used in 87.9% and 88.5% of treatment courses, respectively. From the early (2018–2022) to late (2022–2026) study period, the proportion of fractions utilizing SBRT (49.9% vs. 81.1%; p < 0.001), oART (32.9% vs. 80.2%; p < 0.001), respiratory gating (75.9% vs. 88.8%; p < 0.001), and elective nodal coverage (61.8% vs. 78.2%; p < 0.001) increased, as did the proportion of pancreatic treatments (20.4% vs. 38.4%; p < 0.001) and the utilization of single-fraction courses (3.4% vs. 10.3%; p < 0.001). Despite this increasing complexity between study periods, median oART TIRT decreased from 67.0 to 48.0 min (28.4% reduction; p < 0.001), driven primarily by a reduction in TAT from 20.0 to 7.0 min, p < 0.001. Pancreatic oART fractions showed the greatest improvement (median TIRT, 70.0 to 47.0 min; p < 0.001). In 2022–2026, 78.1% of oART fractions were completed within 60 min vs. 35.5% in 2018–2022 (p < 0.001). Conclusions: Ablative MRgRT, with or without oART, can often be delivered in 60 min or less, including for mobile and anatomically unfavorable tumors. Future software and hardware advances are expected to further improve MRgRT treatment efficiency.